MWCNT reinforced hydrogen nitrile butadiene rubber (HNBR) nanocomposites - Chan, Pei Yen (2014)
HNBR is well-known for its physical strength as well as its retention properties after long-term exposure to chemicals, heat, and oil. HNBR is the fastest growing specialty elastomer in the last decade. HNBR unique properties have resulted in its wide acceptance in automotive, industrial, and assorted, performance-demanding applications. The automotive market is the largest consumer of HNBR on a volume basis. Automotive industry uses HNBR for a host of dynamic and static seals, hoses, and belts. Oil and gas industry has also widely employed HNBR in industrial sealing for oil field exploration and processing. Other usage of HNBR can be seen in rolls for steel and paper mills. HNBR is the ideal choice for applications that required heat, oil and chemical resistance as well as excellent physical properties. Another benefit is its excellent cost effectiveness for the most demanding applications. However, due to the technology advances nowadays, even HNBR is not able to satisfy the industrial requirements. A way to improve the properties of rubbers is through the fabrication of composites. Polymer composite is defined as composite in which at least one component is a polymer while nanocomposite is defined as composite in which at least one of the phases has at least one dimension of the order of nanometers. Small amount of fillers, as known as reinforcing phase, introduced into the matrix can result in a dramatic change in nanocomposites properties. Moreover, rubber composites have been successful in several applications such as automotive tyre. HNBR is a versatile rubber material because of the combination of abrasion resistance, fluid resistance and toughness. Thus, a potential product that can fill the gap in the increasing demand of rubber materials may be satisfied by rubber nanocomposites.